2012
DOI: 10.1590/s1415-47572012000600008
|View full text |Cite
|
Sign up to set email alerts
|

The TP53 fertility network

Abstract: The TP53 gene, first described in 1979, was identified as a tumor suppressor gene in 1989, when it became clear that its product, the p53 nuclear phosphoprotein, was frequently inactivated in many different forms of cancers. Nicknamed “guardian of the genome”, TP53 occupies a central node in stress response networks. The p53 protein has a key role as transcription factor in limiting oncogenesis through several growth suppressive functions, such as initiating apoptosis, senescence, or cell cycle arrest. The p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
0
15
1
Order By: Relevance
“…Compared to its role in apoptosis, the role of p53 in cellular senescence is far from clear. As p53 is an important transcription factor and directly regulates numerous genes , it is unclear which of the p53 targets are part of the p53 downstream pathway that mediates induction of senescence. Hearnes et al identified >100 potential p53 downstream target genes using a chromatin immunoprecipitation (ChIP) assay, including known p53 targets as well as novel potential target genes, including UBTD1 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to its role in apoptosis, the role of p53 in cellular senescence is far from clear. As p53 is an important transcription factor and directly regulates numerous genes , it is unclear which of the p53 targets are part of the p53 downstream pathway that mediates induction of senescence. Hearnes et al identified >100 potential p53 downstream target genes using a chromatin immunoprecipitation (ChIP) assay, including known p53 targets as well as novel potential target genes, including UBTD1 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a binding site for MEF2A has been linked to formal thought disorder (Thygesen et al 2015). Likewise, TP53 exhibits a non-fixed change (P72R) compared to Neanderthals/Denisovans (Paskulin et al 2012) and the expression pattern of the human gene differs from the patterns observed in other primates (Konopka et al 2012). Risk alleles for TP53 seem to contribute to the reduced metabolic activity and the reduced white matter volumes observed in the frontal lobe of schizophrenics (Molina et al 2011).…”
Section: Core Candidate Genes For Language Evolutionmentioning
confidence: 98%
“…Additionally, both transcription factors compete for common cofactors (Wadgaonkar et al, 1999). Therefore, hyperactive NF-κB prote B reduces the tumor suppressor activity of p53 leading to oncogene-mediated transformation (Gudkov et al, 2011), because p53 contributes to the maintenance of the differentiated state and restrain dedifferentiation (Molchadsky et al, 2010;Paskulin et al, 2012). Lower p53 levels improve reprogramming efficiency of somatic cells into induced pluripotent stem cells (Kawamura et al, 2009).…”
Section: Chronic Inflammation In the Process Of Agingmentioning
confidence: 99%